Return to Play after Arthroscopic Bankart Repair Combined with Open Subpectoral Biceps Tenodesis - James P. Toale, M.B., B.Ch; Eoghan T. Hurley, M.B., B.Ch., M.Ch; Martin S. Davey, M.B., B.Ch., M.Ch; J. Tristan Cassidy, M.Ch., F.R.C.S.I. (Tr & Orth); Leo Pauzenberger, M.D; Hannan Mullett, M.Ch., F.R.C.S.I. (Tr & Orth) (Elsevier, 2020)
Purpose: To evaluate the clinical outcomes and rate of return to play (RTP) in patients who underwent arthroscopic Bankart repair and open subpectoral biceps tenodesis. Methods: A retrospective review of patients who underwent combined arthroscopic Bankart repair and open subpectoral biceps tenodesis by a single surgeon between 2012 and 2016 was performed. RTP, the level of return, and the timing of return were assessed. Visual analog scale for pain, Rowe score, Shoulder Instability-Return to Sport after Injury score, and Subjective Shoulder Value were evaluated. Results: The study included 14 patients, with a mean follow-up of 34.2 ± 12.1 months. Of the 14 patients, 13 (92.9%) returned to sport at a mean of 4.8 ± 1.2 months and 9 (64.3%) returned to the same or higher level of sport. At final follow-up, the mean Rowe was 80.0 ± 16.3, the mean Subjective Shoulder Value was 81.0 ± 15.1, the mean Shoulder Instability-Return to Sport after Injury was 57.3 ± 25.6, and the mean visual analog scale score was 2.6 ± 1.5. One patient had a recurrent dislocation, whereas no patients underwent a further operation on the ipsilateral shoulder. Conclusion: Patients undergoing arthroscopic Bankart repair combined with open subpectoral biceps tenodesis had a high rate of RTP with a low rate of recurrent instability. Level of Evidence: IV, Therapeutic Case Series.